Human Development Index, Capital Expenditure, Fiscal Desentralization to Economic Growth and Income Inequality in East Java Indonesia - Novid, Ade; Sumarsono, Hadi (Quantitative Economics Research, 2018)
This study aims to determine the effect of the Human Development Index, Capital Expenditure, Fiscal Decentralization Against Economic Growth and Income Inequality in East Java in Indonesia. This study applied a quantitative approach using a combination between time series and data between place and space (cross-section), to determine whether there is a relationship between two variables or better direct or indirect influence. The findings indicated that the index of human development (HDI) and capital expenditure have a positive and significant impact on economic growth. The higher Human Development Index and capital expenditure affect the greater economic growth rate. However, the degree of fiscal decentralization does not influence economic growth, while economic growth has a positive effect and significant effect on income inequality. Inter-regional economic growth showed varies, in increasing per capita income in some areas of high economic growth, while some other regions have low economic growth, resulting in increased income inequality. Keywords: Human Development Index, Capital Expenditure, Fiscal Decentralization, Economic GrowthJEL Codes: E62; O15; R11